2021
DOI: 10.3390/app11198973
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Roof Rocks under Superimposed Static and Dynamic Loads with Medium Strain Rates in Coal Mines

Abstract: Roof rocks in coal mines are subjected to the combination of in situ stresses and dynamic stresses induced by mining activities. Understanding the mechanical properties of roof rocks under static and dynamic loads at medium strain rates is of great significance to revealing the mechanism of rock bursts. In this study, we employ the digital image correlation (DIC) technique to investigate the energy concentration and dissipation behaviors, failure mode, and deformation characteristics of roof rocks under combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The triaxial stress-strain curve and a photo after the failure of a typical specimen are shown in Figure 3. The failure mode under the true triaxial conditions was mainly shear failure and a significant large crack ran through the samples from top to bottom and, compared with uniaxial compression, the total number of cracks was relatively small, which is similar to the results by Zhao [45] and Zhong [46]. The numerical simulation software FLAC3D was adopted for the simulation.…”
Section: Strength Parameters Of Coalsupporting
confidence: 67%
“…The triaxial stress-strain curve and a photo after the failure of a typical specimen are shown in Figure 3. The failure mode under the true triaxial conditions was mainly shear failure and a significant large crack ran through the samples from top to bottom and, compared with uniaxial compression, the total number of cracks was relatively small, which is similar to the results by Zhao [45] and Zhong [46]. The numerical simulation software FLAC3D was adopted for the simulation.…”
Section: Strength Parameters Of Coalsupporting
confidence: 67%
“…Considering the effect of dynamic disturbance on the coal body of the isolated working face by mining activities Mathematical Problems in Engineering 5 [32,33], introducing the dynamic load coefficient k, the average stress of the working face is shown in…”
Section: Strike Abutment Pressure Distribution Characteristicsmentioning
confidence: 99%
“…The results showed that the uniaxial compressive strength, tensile strength, and fracture toughness of gas-containing coal decreased with the increase in initial gas pressure. Currently, most of the studies on the mechanical properties of gas-containing coals are inclined to static mechanics, but in the mining of coal resources, artificial disturbances such as fracture of the roof slab overlying the mining area and rock blasting will produce apparent dynamic phenomena. The coal body, in this case, will be subjected to dynamic loads along with tectonic stresses and pore pressure in the coal body. When coal/rock is subjected to the multifield coupling effect of underground stress, gas pressure, and quarry disturbance stress, it is easy to trigger the occurrence of disasters such as rock burst or coal and gas outburst.…”
Section: Introductionmentioning
confidence: 99%